2017
DOI: 10.1002/dneu.22564
|View full text |Cite
|
Sign up to set email alerts
|

SHANK1 is differentially expressed during development in CA1 hippocampal neurons and astrocytes

Abstract: Recent studies have strongly suggested a role for the synaptic scaffolding protein SHANK1 in normal synaptic structure and signaling. Global SHANK1 knockout (SHANK1-/-) mice demonstrate reduced dendritic spine density, an immature dendritic spine phenotype and impairments in various cognitive tasks. SHANK1 overexpression is associated with increased dendritic spine size and impairments in fear conditioning. These studies suggest proper regulation of SHANK1 is crucial for appropriate synaptic structure and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…SHANK2 and SHANK3 are therefore considered critical for several aspects of neuroplasticity during development [31]. Studies have demonstrated that SHANK1 protein levels increase from birth through early development, followed by a slight decrease in adulthood in the cerebellum and cortex [32]. In fact, SHANK1-3 protein components represent critical determinants of excitatory synaptic function.…”
Section: Shank Proteins At Postsynaptic Densitymentioning
confidence: 99%
“…SHANK2 and SHANK3 are therefore considered critical for several aspects of neuroplasticity during development [31]. Studies have demonstrated that SHANK1 protein levels increase from birth through early development, followed by a slight decrease in adulthood in the cerebellum and cortex [32]. In fact, SHANK1-3 protein components represent critical determinants of excitatory synaptic function.…”
Section: Shank Proteins At Postsynaptic Densitymentioning
confidence: 99%
“…SHANK proteins are mainly localized in the postsynaptic densities (PSD) domain of neuronal excitatory synapses in the central nervous system. At present, it is believed that the SHANK family is essential for the normal function of the nervous system [ 2 4 ]. An association between cases of autism spectrum disorder (ASD) and mutations in the genes SH3 and multiple ankyrin repeat domains protein 1 (SHANK1), SHANK2 and SHANK3 was reported in several large-scale genomic studies.…”
Section: Introductionmentioning
confidence: 99%